LAILATUL IJTIMA’ NU RANTING JAJAG SEBAGAI LEARNING SOCIETY - Mashuri, Imam (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
Lailatul Ijtima'NU Jajag branch as a forum for the learning society of the Jajag community which includes religious and educational aspects, as well as a means of helping to reduce and solve problems in society, both local and national issues. This service is carried out using lecture and discussion methods. The results of this activity transformed the values ​​of religious aspects and educational aspects among NU residents, sympathizers and the surrounding community. It is hoped that in the future NU residents in particular and society in general will be able to preserve NU traditions and practices and be able to solve problems by prioritizing kinship in accordance with the concepts of I'tidal, Tawazun, Tasamuh and Tawasut.